ChemInform Abstract: 2, 2′‐Biphenols via Protecting Group‐Free Thermal or Microwave‐Accelerated Suzuki—Miyaura Coupling in Water. Issue 5 (4th February 2014) - Schmidt, Bernd; Riemer, Martin; Karras, Manfred
Abstract These methods use simple conditions with readily available catalysts and reagents.